Transport of L-glutamic acid in the fission yeast Schizosaccharomyces pombe - Rezková, K; Horák, J; Sychrová, H; Kotyk, A (Biochimica et biophysica acta, 1992)
Transport of L-glutamic acid into the fission yeast Schizosaccharomyces pombe grown to the early stationary phase and preincubated for 60 min with 1% D-glucose is practically unidirectional and is mediated by a single uphill transport system with a KT of 170 microM and Jmax of 4.8 nmol min-1 (mg dry wt.)-1. The system proved to be rather non-specific since all the amino acids transported into the cells acted as potent competitive inhibitors. It has a pH optimum at 3.0-4.0, the accumulation ratio of L-glutamic acid is highest at a suspension density of 0.6-1.0 mg dry wt. per ml and decreases with increasing L-glutamic acid concentrations in the external medium. The system present in the cells after preincubation with D-glucose is unstable and its activity decays after washing the cells with water or after stopping the cytosolic proteinsynthesis with cycloheximide, with a half-time of 24 min in a reaction significantly retarded by phenylmethylsulfonyl fluoride, a serine proteinase inhibitor. The synthesis of the transport protein appears to be repressible by ammonium ions.
Keywords: cykloheximid; Substrate Specificity; glutamáty; fungální proteiny; Glutamic Acid; Schizosaccharomyces; Glutamates; transportní proteiny; Carrier Proteins; Kinetics; biologický transport; Cycloheximide; substrátová specifita; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; kinetika; Biological Transport; kyselina glutamová; Fungal Proteins